Gas Emissions in a Transtensile Regime Along the Western Slope of the Mid-Okinawa Trough - Li, Ang; Cai, Feng; Wu, Nengyou; Li, Qing; Yan, Guijing; Sun, Yunbao; Dong, Gang; Luo, Di; Wang, Xingxing (Frontiers in Earth Science, 2021)
Gas emissions from the seabed are favored by tectonically active settings and their distribution is often linked to the nearby faults. Here we use the multi-beam echo-sounder (MBES) and the multi-channel seismic (MCS) data and a sediment core to show multiple gas emissions near the fault complex out of the shelf of the Mid-Okinawa Trough. The features indicating the gas emissions include (a) a set of the conical positive reliefs at the seabed, (b) the bundle-shaped clusters of the high-backscattering intensities in the water column, and (c) the sub-circular medium- to high-backscattering patches at the level of the seabed. These features together show that the free gases can escape from the marine sediments then rise in the water column at present, while some other gases trapped in the sub-seafloor sediment might contribute to the precipitation of the authigenic carbonates in the past. The spatial relationship between the gas emissions and the faults suggests that the faulting driven by the back-arc extension should provide the permeable migration pathways for the gas emissions to operate, and thus determines where most of them could potentially occur. The area surrounding the restraining bend concentrates part of the gas emissions rather than along the fault lines, due to the lateral compression and the structural complexity. This is demonstrated by the results of the numerical model of finite element method (FEM), which shows two gas emissions are within the compressed zone of the modeled restraining step-over. This study provides new evidence of the role of the tectonic stresses in determining the sites of degassing of marine sediments.